Model Pembelajaran CORE (Connecting, Organizing, Reflecing, Extending) Untuk Meningkatkan Hasil Belajar Di Sekolah Dasar: SLR - wahyu sugiati; Wahyu Sugiati (Universitas Sebelas Maret, 2026)
Elementary school students' learning outcomes remain a concern because the learning process tends to be teacher-centered, resulting in suboptimal student engagement in constructing knowledge. The CORE (Connecting, Organizing, Reflecting, Extending) learning model, based on constructivism theory, has the potential to create active and meaningful learning to improve learning outcomes. This study aims to analyze the implementation of the CORE learning model in improving elementary school students' learning outcomes using the Systematic Literature Review method following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Data were obtained from Google Scholar, Semantic Scholar, and Scopus in publications from 2020–2025. A total of 15 articles that met the inclusion criteria were analyzed using narrative synthesis techniques. The results showed that the implementation of the CORE learning model consistently improved student learning outcomes, as indicated by an increase in the average value of learning outcomes, percentage of learning completion, and statistical test results in the reviewed studies. The CORE stages encourage students to connect prior knowledge, build concepts, reflect on understanding, and develop knowledge in new situations so that learning becomes more meaningful. These findings indicate that the CORE learning model can be used as an alternative learning model to improve elementary school students' learning outcomes and as a reference for teachers in selecting learning models and for researchers in developing further research